THE INFLUENCE OF THE PROBLEM-BASED INSTRUCTION MODEL BASED ON VIDEO MEDIA AND EDUCATIONAL GAMES ON THE SELF-EFFICACY - Gabriella Jessi Sitohang; Ati Sumiati; Santi Susanti (International Research of Multidisciplinary Analysis, 2023)
This study discusses the differences in self-efficacy of class X students at SMK N 17 Jakarta from applying the PBI learning model with the help of two different learning media. The media used in this research are learning videos applied to the experimental class and educational games (quizizz) in the control class. The study aimed to find evidence of whether there was a difference in student self-efficacy after implementing the PBI learning model with the help of two different media. Based on the data hypothesis test conducted by comparing the scores of the self-efficacy between the experimental class and control classes, it was concluded that there was a significant difference between the students' self-efficacy in both classes. The average score of self-efficacy in the experimental class is higher than the control class, so that in the future, the use of learning video media can be one of the best alternatives when implementing the PBI learning model to support student self-efficacy